The advocate’s own challenges to behave in a sustainable way: an Institutional analysis of advocacy NGOs - Koster, M.; Simaens, A.; Vos, B. (Journal of Business Ethics, 2019)
Non-governmental organizations (NGOs) are increasingly important drivers for businesses’ self-regulation to operate in a sustainable way. We shift the perspective on NGOs from focusing on their advocacy role to focusing on their accountability for having sustainable internal operations. In a multiple case analysis, we explore the question ‘What are the drivers and barriers to sustainable conduct of NGOs that are sustainability advocates?’ Drawing on institutional theory, we obtain novel insights into the legitimacy-seeking motivations for sustainable conduct in the specific context of advocacy NGOs. We found that, affected by its mission, (1) the cultural-cognitive drive is particularly high, with sustainable conduct as an internally ‘taken-for-granted’ behavior, followed by (2) the normative drivers, with the balance between perceived vulnerability of needing to ‘walk the talk’ and the sense of immunity due to lack of external scrutiny, and (3) there are hardly any regulative drivers. Furthermore, these organizations face idiosyncratic trade-offs when balancing investments in their advocacy missions with investments in sustainable operations, reflecting ethical dilemmas. In a broader sense, this research elucidates the way advocates cope in situations of institutional complexity, with conflicting institutional demands between their mission and role-model function.